Mobile-Assisted Pronunciation Training: The Google Play Pronunciation and Phonetics Application - Fitria Meisarah (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: Several obstacles to pronunciation have been proposed and urged students to practice pronunciation deliberately. Regardless of these problematic, mobile applications can be a great assistant in pronunciation training. However, considering that Google Play is the most prominent android app store with 227,970 instructional devices, it is challenging to find and select pronunciation and phonetics applications. Students should be conscious of their needs by recognizing the proper mobile application for pronunciation learning. This study explores the pronunciation applications utilized by students for pronunciation learning in and out of the classroom. Methodology: This study administered the data with paper reports and interviews accompanying students. This study involved 41 students who were taking a pronunciation and phonetics course at the University of Kutai Kartanegara Tenggarong. Findings: Nine such applications, as reviewed in this study, are divided into two categories: English pronunciation special purpose (EPSP) application and English dictionary assisted pronunciation (EDAP) application. Noteworthy findings were not all of the applications fulfill the content and design approaches such the suprasegmental features, audio playback, and video camera recorder. Conclusion: This study endeavors to have a critical look at four applications recommended after concerning the term of Mobile Assisted Pronunciation Training (MAPT). They are AV Phonetic, English Phonetic Pronunciation, Listening Practice, English Pronunciation developed by Kepham, and U-Dictionary to assist pronunciation learning in and out of the classroom. Keywords: Pronunciation and phonetics; mobile application; MAPT